2021
DOI: 10.1055/s-0041-1733791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Delirium

Abstract: Delirium, sometimes referred to as encephalopathy, is an acute confusional state that is both common in hospitalized patients and associated with poor outcomes. For patients, families, and caregivers, delirium can be a traumatic experience. While delirium is one of the most common diagnoses encountered by the consulting neurologist, the majority of the time it will have been previously unrecognized as such by the care team. Neurologic syndromes such as dementia or aphasia can either be misdiagnosed as delirium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Some healthcare professionals were less familiar with specific risk factors for delirium, e.g., vision impairment, being male, a dementia diagnosis and having an internal device such as a urinary catheter (Hare et al, 2008;Meako et al, 2011;Rosado et al, 2019). Some healthcare professionals did not know if their hospital organization had a delirium management protocol in place and in two studies participants were unsure about the treatment pathway (Limpawattana et al, 2018;Ryan & Milligan, 2017). Doctors reported that their nursing colleagues lacked knowledge about delirium care, especially non-pharmacological interventions, and that this contributed to an increase in the use of pharmacological interventions or restraint (Van de Steeg et al, 2014).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some healthcare professionals were less familiar with specific risk factors for delirium, e.g., vision impairment, being male, a dementia diagnosis and having an internal device such as a urinary catheter (Hare et al, 2008;Meako et al, 2011;Rosado et al, 2019). Some healthcare professionals did not know if their hospital organization had a delirium management protocol in place and in two studies participants were unsure about the treatment pathway (Limpawattana et al, 2018;Ryan & Milligan, 2017). Doctors reported that their nursing colleagues lacked knowledge about delirium care, especially non-pharmacological interventions, and that this contributed to an increase in the use of pharmacological interventions or restraint (Van de Steeg et al, 2014).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Some healthcare professionals did not know if their hospital organization had a delirium management protocol in place and in two studies participants were unsure about the treatment pathway (Limpawattana et al., 2018; Ryan & Milligan, 2017). Doctors reported that their nursing colleagues lacked knowledge about delirium care, especially non‐pharmacological interventions, and that this contributed to an increase in the use of pharmacological interventions or restraint (Van de Steeg et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, Z-score was calculated by the following way: ([change score] individual -[mean change score])/(standard deviation change score total ) [ 25 , 26 ]. The diagnosis of postoperative delirium (POD) employed CAM-ICU on postoperative days 3 and 7 [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the more robust approach to behavioural dysregulation, whether caused by delirium or other factors, should involve investigation of and mitigation of precipitating causes. Indeed, ongoing research into the management of delirium recognises the key role of diagnosing the underlying cause of the patient’s acute confusional state and treating the underlying cause, with support of other non-pharmacological interventions before new medications are initiated 27 28…”
Section: Possible Avenues To Improve Medication Safety In Long-term Carementioning
confidence: 99%